Forecasting and communicating the dispersion and fallout of ash during volcanic eruptions: lessons from the September 20, 2020 eruptive pulse at Sangay volcano, Ecuador - Bernard, Benjamin; Samaniego, Pablo; Mastin, Larry; Hernandez, Stephen; Pino, Gerardo; Kibler, Jamie; Encalada, Marjorie; Hidalgo, Silvana; Vizuete, Nicole (Frontiers in Earth Science, 2022)
Volcanic ash is a hazard to human health and activities. Accurate and timely forecasts coupled with effective communication about the dispersion and fallout of volcanic ash during explosive events are essential to reduce impacts on local communities and limit economic losses. In this study, we evaluate the protocol developed by the Instituto Geofísico de la Escuela Politécnica Nacional (IG-EPN) of Ecuador. We present the first detailed description of an eruptive pulse at Sangay volcano and its eruption source parameters. The eruptive pulse on September 20, 2020, started at about 9:20 UTC and lasted between 90 and 100 minutes, producing an eruptive column that rapidly separated into (1) a higher (15.2 km asl, above sea level), gas-rich cloud moving east-southeast and (2) a lower (12.2 km asl), ash-rich cloud moving west and causing ash fallout up to 280 km from the volcano. Field data collected immediately after the event allow estimating the volume of bulk tephra to be between 1.5 and 5.0E+6 m3, corresponding to a volcanic explosivity index of 2. The eruptive pulse, identified as violent Strombolian, emitted andesitic ash that was more mafic than products ejected by Sangay volcano in recent decades. Component analysis and glass chemistry of juvenile particles support the hypothesis that this event excavated deeper into the upper vent compared to typical Strombolian activity at Sangay volcano, while grain-size analysis allows reconstruction of the total grain-size distribution of the fallout deposit. The field results help to explain discrepancies between the three eruptive scenarios simulated during the event using the Ash3D online tool and the actual deposit, and confirm the usefulness of the simulations to guide early warnings. IG-EPN communication during the event included the dissemination of (1) several standard short reports, (2) Volcano Observatory Notices for Aviation, (3) social media posts on IG-EPN accounts, and (4) a special report providing the results of the volcanic cloud simulation using the Ash3D online tool. Although communication was effective with the authorities and the connected population, allowing early humanitarian actions to be triggered, an effort must be made to reach the most vulnerable isolated communities.